Far beyond the planar limit in strongly-coupled $$ \mathcal{N} $$ = 4 SYM - Chester,SM; Pufu,SS (Journal of High Energy Physics, 2021)
A bstract When the SU( N ) $$ \mathcal{N} $$ N = 4 super-Yang-Mills (SYM) theory with complexified gauge coupling τ is placed on a round four-sphere and deformed by an $$ \mathcal{N} $$ N = 2-preserving mass parameter m , its free energy F ( m, τ, $$ \overline{τ} $$ τ ¯ ) can be computed exactly using supersymmetric localization. In this work, we derive a new exact relation between the fourth derivative $$ {\partial}_m^4F\left(m,τ, \overline{τ}\right)\left|{{}_m}_{=0}\right. $$